Bytový dům - Kubů, Michal (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Cílem bakalářské práce je návrh bytového domu ve městě Humpolec v kraji Vysočina. Objekt je řešen jako samostatně stojící se třemi nadzemními podlažími a plným podsklepením. V objektu se nachází 6 samostatných bytových jednotek z nichž jedna je řešena jako bezbariérová. Hlavní nosný systém je navržen z keramického zdiva. Suterénní zdivo je z betonových tvárnic ztraceného bednění. Střecha bytového domu je navržena jako plochá. Projektová dokumentace byla zhotovena dle platných právních a technických předpisů.

The aim of a bachelor thesis is design of a apartment building in Humpolec in Highlands Region. The building is designed as a detached building with three above-ground floors and a full basement. The building has six separate apartment units, one of which is designed as barrier-free. The main support system is designed from ceramic masonry. Basement masonry is made of the permanent concrete formwork. The roof of the apartment building is designed as flat. Project documentation was prepared according to valid legal and technical regulation.
Apartment building
Keywords: Bytový dům; Humpolec; bytové jednotky; tři nadzemní podlaží; plochá střecha; Apartment building; Humpolec; apartment units; three above-ground floors; flat roof